2021
DOI: 10.1111/mmi.14783
|View full text |Cite
|
Sign up to set email alerts
|

Burkholderia multivorans requires species‐specific GltJK for entry of a contact‐dependent growth inhibition system protein

Abstract: Interbacterial antagonism and communication are driving forces behind microbial community development. In many Gram‐negative bacteria, contact‐dependent growth inhibition (CDI) systems contribute to these microbial interactions. CDI systems deliver the toxic C‐terminus of a large surface exposed protein to the cytoplasm of neighboring bacteria upon cell−contact. Termed the BcpA‐CT, import of this toxic effector domain is mediated by specific, yet largely unknown receptors on the recipient cell outer and inner … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Toward understanding the mechanism of Burkholderia CDI system effector import, we sought to identify recipient cell factors necessary for susceptibility to these two active CDI systems. A B. dolosa mutant lacking both CDI system-1 and CDI system-2 (Δ bcp-1 Δ bcp-2 ) was mutagenized using a miniTn5-based transposon and serially competed against B. dolosa donor cells that produced either CDI system-1 (Δ bcp-2 ) or CDI system-2 (Δ bcp-1 ), as previously described ( 15 ). Transposon insertion sites identified from resistant clones found one unique insertion site, in gene BDAG_00967, from individual colonies resistant to CDI system-2 (Table S5).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Toward understanding the mechanism of Burkholderia CDI system effector import, we sought to identify recipient cell factors necessary for susceptibility to these two active CDI systems. A B. dolosa mutant lacking both CDI system-1 and CDI system-2 (Δ bcp-1 Δ bcp-2 ) was mutagenized using a miniTn5-based transposon and serially competed against B. dolosa donor cells that produced either CDI system-1 (Δ bcp-2 ) or CDI system-2 (Δ bcp-1 ), as previously described ( 15 ). Transposon insertion sites identified from resistant clones found one unique insertion site, in gene BDAG_00967, from individual colonies resistant to CDI system-2 (Table S5).…”
Section: Resultsmentioning
confidence: 99%
“…According to the current model, intoxication via the CDI system protein BcpA requires both extracellular and intracellular proteins to facilitate translocation into the recipient cell cytoplasm. Inner membrane proteins GltJK and Bth_II0599 have been found to facilitate translocation of BcpA-CT from B. multivorans and B. pseudomallei , respectively ( 15 , 16 ). This study has not identified candidate inner membrane receptors for B. dolosa BcpA-1 or BcpA-2, potentially due to a lack of saturation in the mutagenesis scheme or essentiality of the receptor encoding genes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations